Obesity as a clinical predictor for severe manifestation of dengue: a systematic review and meta-analysis - Chen, Chao-Ying; Chiu, Yu-Yao; Chen, Yu-Cheng; Huang, Chung-Hao; Wang, Wen-Hung; Chen, Yen-Hsu; Lin, Chun-Yu (BMC infectious diseases, 2023)
Severe dengue often leads to poor clinical outcomes and high mortality; as a result, it is of vital importance to find prognostic factors associated with the severe form of dengue. Obesity is known to deteriorate many infectious diseases due to impaired immune responses. Several studies have suggested that obese patients with dengue infection tend to have more severe manifestations with poorer prognosis. However, a firm conclusion could not be drawn due to the varied results of these studies. Here, we aimed to conduct a systematic review and meta-analysis to investigate the association between obesity and dengue severity. A literature search for relevant studies was conducted in PubMed, Embase, Ovid Medline and Cochrane from inception to September 9, 2022. The two main keywords were "dengue" and "obesity". Mantel-Haenszel method and random effects model was used to analyze the pooled odds ratio with 95% confidence intervals. A total of 15 article involving a total of 6,508 patients were included in the meta-analysis. Included patients in most studies were hospitalized pediatric patients. Only one study included adulthood data. Three cohort studies, four case-control studies, and one cross-sectional studies found a significant association between obesity and dengue severity. In contrast, three cohort studies, three case-control studies, and one cross-sectional study reported no significant relationship between obesity and dengue severity. Our analysis results showed that patient with obesity is 50% (OR = 1.50; 95%CI: 1.15-1.97) more likely to develop severe manifestation of dengue. This meta-analysis revealed that overweight could be a clinical predictor for severe disease for pediatric patients with dengue infection.